REVISITING THE QUALITY OF GAS FUEL - Koliyenko, A.; Shelimanova О.; Koliyenko, V. (Energy and Automation, 2016)
It is noted that the quality of natural gas and the stability of the physical and chemical parameters is a fundamental component of an effective and safe operation palyvospalyuyuchoho equipment. Particular attention should be paid to the change in the heat of the combustion gas density and criteria for interchangeability. language:EN’>The article shows application of the method of the research robust stability of the closed-loop system of the example multidimensional object of management – the dryer fluidized bed, the design of which was developed in Kirovograd national technical University.